Dynamic Interval-Valued PCA for Enhanced Fault Detection - Rouani, Lahcene; Harkat, Mohamed Faouzi; Kouadri, Abdelmalek; Bensmail, Abderazak; Mansouri, Majdi; Nounou, Mohamed (International Conference on Control, Decision and Information Technologies (Online), 2024)
This study introduces three novel dynamic interval-valued principal component analysis (DIPCA) methods: dynamic centers PCA (D-CPCA), dynamic vertices PCA (D-VPCA), and dynamic complete information PCA (D-CIPCA). These methods advance traditional interval-valued PCA (IPCA) by integrating dynamic aspects of industrial processes, thus addressing both data uncertainties and temporal correlations. The DIPCA methods were validated using real-world data from the Ain El Kebira cement plant. Results indicate significant improvements in fault detection accuracy, achieving lower false alarm rates and higher reliability compared to classical IPCA methods. Furthermore, an enhanced combined index for interval-valued data was developed, providing a single, comprehensive statistical measure for streamlined process monitoring.